Submarine Active Faults and Morpho-Tectonics Around the Iberian Margins: Seismic and Tsunamis Hazards - Somoza, Luis; Medialdea, Teresa; Terrinha, Pedro; Ramos, Adrià; Vázquez, Juan-Tomás (Frontiers in Earth Science, 2021)
The aim of this work is to make a synthesis at regional scale focused on the geophysical characterization of submarine faults around the Iberian margin to identify active structures and analyze their development in the framework of the present plate organization. Most of these submarine faults show seabed morphological expressions mapped with high-resolution swath bathymetry data, high-resolution parametric sub-bottom profiles and multichannel seismic profiles. Present active tectonics, deformation, seismicity and tsunami-affected coastal areas is mainly focused on south Iberia at the Eurasian and Nubia plate boundary. Submarine active faults in these areas are represented by long strike-slip fault systems and arcuate fold-thrust systems. Their development takes place in response to present NW-SE convergence between the Eurasian and Nubia plates. We propose a strain partitioning model of the plate boundary into simple and pure shear zones to explain the distribution and mechanisms of active submarine faults along the Gulf of Cádiz, Gibraltar Arc and Alborán Sea in response to the present-day shear stress orientation. Nevertheless, deformation is also focused in the NW Iberian margin. Thus, along the Galician and Portuguese margin, several submarine faults mapped as thrust fault systems with high-seismic activity along the Iberian ocean-continent transition reflect the re-activation of former structures. We suggest that submarine active faults in the NW and W Iberia are also the response to the westwards transfer of short-offset transform faults of the Mid Atlantic Ridge into the oceanic Iberian along a weakness as the former plate boundary between the oceanic Iberia and Eurasia domains. The distribution and activity of submarine faults mapped in this work from geophysical and bathymetric data are in good agreement with geodetic data and focal mechanisms.